Unveiling Consumer Affection: Exploring the Psychological Forces Driving Love and Willingness to Pay for Premium Laptop Brands - Nofrizal; Arizal N; Aznuriyandi; Nurhayani Lubis; Mohammad Tahir Zainuddin (Fakultas Ekonomika dan Bisnis Universitas, 2024)
Non-Indexed Publication